Evaluation of the efficacy and safety of olanzapine as an adjunctive treatment for anorexia nervosa in adolescent females: a randomized, double-blind, placebo-controlled trial - Moher David; Feder Stephen; Henderson Katherine; Buchholz Annick; Spettigue Wendy; Kourad Kader; Gaboury Isabelle; Norris Mark; Ledoux Sheila (BMC, 2008)
Abstract Background Anorexia Nervosa (AN) is a serious, debilitating condition that causes significant physical, emotional, and functional impairment. The condition is characterized by destructive weight loss behaviours and a refusal to maintain body weight at or above a minimally normal weight for age and height. AN often develops in adolescence and is a predominantly female disorder. Treatment for AN typically involves medical, nutritional and psychological interventions. Pharmacotherapy is also often used; however, the literature on the effectiveness of these drugs in a pediatric population is very limited. Olanzapine, which is an 'atypical' antipsychotic, is becoming more widespread in the treatment of AN. Olanzapine is hypothesized to facilitate weight gain, while decreasing levels of agitation and decreasing resistance to treatment in young women with AN. This randomized, double-blind placebo-controlled trial seeks to examine the effectiveness and safety of olanzapine in female youth with AN. Methods/Design Adolescent females between the ages of 12 and 17 diagnosed with AN (either restricting or binge/purge type) or Eating Disorder Not Otherwise Specified with a Body Mass Index of less than or equal to 17.5, will be offered inclusion in the study. Patients will be randomly assigned to receive either olanzapine or placebo. Patients assigned to receive olanzapine will start at a low dose of 1.25 mg/day for three days, followed by 2.5 mg/day for four days, 5 mg/day for one week, then 7.5 mg/day (the target dose chosen) for 10 weeks. After 10 weeks at 7.5 mg the medication will be tapered and discontinued over a period of two weeks. The effectiveness of olanzapine versus placebo will be determined by investigating the change from baseline on measures of eating attitudes and behaviors, depression and anxiety, and change in Body Mass Index at week 12, and after a follow-up period at week 40. It is anticipated that 67 participants will be recruited over two years to complete enrollment. Discussion Randomized controlled trials designed to measure the safety and effectiveness of olanzapine in comparison to placebo are desperately needed, particularly in the adolescent population. Trial registration Current Controlled Trials ISRCTN23032339